The Use of High Sensitivity C-Reactive Protein in Cardiovascular Disease Detection - Ana Rita Castro; Sara Oliveira Silva; Sandra Clara Soares (Frontiers Media S.A., 2018)
Cardiovascular diseases (CVDs) are responsible for a high mortality rate worldwide. One of the most common causes of CVDs is vascular inflammation associated to atherosclerosis. Inflammatory biomarkers are used to assist the detection of CVDs and monitor their evaluation, prognosis and therapy implementation. C-reactive protein (CRP) is an acute phase protein produced after stimulation by pro-inflammatory cytokines. CRP is a biomarker of the inflammatory reaction and an important mediator of atherosclerosis. Given it actively contributes to the development of the atherosclerotic plaque, instability and subsequent clot formation it is also considered a CVD risk factor. Since 2010, the plasma concentration of hsCRP (high sensitivity CRP) has been used as a biomarker for disease prognosis in patients with intermediate risk for CVDs. It could be useful to establish a high concentration limit of hsCRP that can be used by clinicians for diagnosis of acute myocardial infarction, cardio embolic or ischemic stroke, and hypertrophic cardiomyopathy. The end cost/effectiveness of hsCRP screening is still an area of controversy but it is a priority to make the medical community aware of the positive relation between high hsCRP and CVDs to improve median survival and life quality of the patients.